Increasing mitochondrial ATP synthesis with butyrate normalizes ADP and contractile function in metabolic heart disease. (17th February 2020) - Panagia, Marcello; He, Huamei; Baka, Tomas; Pimentel, David R.; Croteau, Dominique; Bachschmid, Markus M.; Balschi, James A.; Colucci, Wilson S.; Luptak, Ivan
Abstract : Metabolic heart disease (MHD), which is strongly associated with heart failure with preserved ejection fraction, is characterized by reduced mitochondrial energy production and contractile performance. In this study, we tested the hypothesis that an acute increase in ATP synthesis, via short chain fatty acid (butyrate) perfusion, restores contractile function in MHD. Isolated hearts of mice with MHD due to consumption of a high fat high sucrose (HFHS) diet or on a control diet (CD) for 4 months were studied using 31 P NMR spectroscopy to measure high energy phosphates and ATP synthesis rates during increased work demand. At baseline, HFHS hearts had increased ADP and decreased free energy of ATP hydrolysis (ΔG ~ ATP ), although contractile function was similar between the two groups. At high work demand, the ATP synthesis rate in HFHS hearts was reduced by over 50%. Unlike CD hearts, HFHS hearts did not increase contractile function at high work demand, indicating a lack of contractile reserve. However, acutely supplementing HFHS hearts with 4mM butyrate normalized ATP synthesis, ADP, ΔG ~ ATP and contractile reserve. Thus, acute reversal of depressed mitochondrial ATP production improves contractile dysfunction in MHD. These findings suggest that energy starvation may be a reversible cause of myocardial dysfunction in MHD, and opens new therapeutic opportunities. Abstract : Obesity induced by high fat high sucrose (HFHS) feeding negatively impacted cardiac energetics (decreased ATP synthesis and decreased |Δ GATP |) and cardiac function, which was unmasked further by increasing demand for cardiac workload (rate pressure product). Acute perfusion of HFHS hearts with butyrate increased the rate of ATP synthesis and improved cardiac energetics and contractile function, thus correcting the lack of contractile reserve in energetically impaired HFHS hearts and indicating a causal relationship between cardiac energetics and cardiac function.